Implementación de un prototipo para detección de atascos vehiculares en los túneles de la ciudad de Guayaquil - Jiménez Paute, Israel (2010)
Presently project is carried out detection of images using the mathematical program MATLAB. In a traffic simulation in a tunnel to scale conformed by two rails, it is carried out detection of vehicles, and it is verified if the vehicles are detained. Using detection of borders and morphological operations the extraction of objects is possible to be able to be compared and to determine if there has been movement of the automobiles in the tunnel. By means of comparison for correlation and for position it is proven if an object has remained in the same place or it has moved. If the vehicle has moved it is possible to obtain the approximate speed to which moved. On the other hand if the vehicle remains during four seconds in the same place an alarm it is sent and the signaling of the rail is changed where that vehicle is, indicating that there has been a jam. When the jam has been solved the signaling of the rail it allows the traffic and the alarm stops.